(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Study the effect of intravenous anesthesia with Ketamine combined Xylazine for limb transplantation surgery. Subjects and methods: 30 pairs of rabbits aged from 1 to 2 years old, indicated for limb replantation surgery, were anesthetized intravenously with Ketamine combined Xylazine. Record the results of induction and maintenance doses, heart rate, respiratory rate, and adverse effects. Results: The induction dose of Ketamine was 5.2 ± 2.8 mg/kg, with Xylazine 1.6 ± 1.2 mg/kg, maintenance dose of Ketamine 5.8±2.6 mg/kg, with Xylazine 1.8±1.5 mg/kg. Conclusion: Intravenous anesthesia with Ketamine and Xylazine was effective, the changes heart rate and respiratory rate were not statistically significant.